2020
DOI: 10.1088/1742-6596/1450/1/012055
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity and effectiveness of nanoemulsion formulas from Piper retrofractum essential oil against brown plant hopper (Nilaparvata lugens Stål)

Abstract: Secondary metabolite compounds of plants have a role as a self-defence against herbivores and pathogens attacks. The objective of research was to study the toxicity, persistence, and effectiveness of extracts and essential oils of Piper retrofractum against brown plant hopper (BPH). Plant extracts were obtained through maceration method using ethyl acetate solvent for P. retrofractum fruit and essential oils obtained by distillation. Extract toxicity testing uses the contact application method. Polo PC program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Both J. curcas and M. fragrans essential oils were transformed into a nanoemulsion formula using a modified low-energy emulsification technique through the phase inversion method, as described by Nuryanti et al (2020). The emulsification process involved the gradual addition of distilled water phase drop by drop into the essentioal oil + Polysorbate phase at a controlled rate of 4 ml per minute.…”
Section: Nanoemulsion Methodsmentioning
confidence: 99%
“…Both J. curcas and M. fragrans essential oils were transformed into a nanoemulsion formula using a modified low-energy emulsification technique through the phase inversion method, as described by Nuryanti et al (2020). The emulsification process involved the gradual addition of distilled water phase drop by drop into the essentioal oil + Polysorbate phase at a controlled rate of 4 ml per minute.…”
Section: Nanoemulsion Methodsmentioning
confidence: 99%
“…Extracts of Daphne mucronata (Thymelaeaceae), Tagetes minuta (Asteraceae), C. procera (Apocynaceae), Boenninghausenia albiflora (Rutaceae), Eucalyptus sideroxylon (Myrtaceae), Cinnamomum camphora (Lauraceae), and Isodon rugosus (Lamiaceae) resulted in different activity against several insect pests species, including pea aphids (Acyrthosiphon pisum) (Hemiptera), fruit flies (Drosophila melanogaster) (Diptera), red flour beetles (Tribolium castaneum) (Coleoptera), and armyworms (Spodoptera exigua)(Lepidoptera) (Khan et al, 2017). Among extracts of Piper retrofractum (Piperaceae), P. crocatum (Piperaceae), Chromolaena odorata (Asteraceae), Tagetes erecta (Asteraceae), Tithonia diversifolia (Asteraceae), and Ageratum conyzoides (Asteraceae), P. retrofractrum extract exhibited the highest mortality compared to the other extracts against Nilaparvata lugens (Nuryanti et al, 2018). Other research results showed that extracts of Citrullus colocynthis (Cucurbitaceae), Cannabis indica (Cannabaceae), and Artemisia argyi (Asteraceae) produced different insecticidal activities and C. colocynthis showed higher insecticidal properties against cabbage aphid (Brevicoryne brassicae) (Ahmed et al, 2020) Recent research used several species of insects from different orders including (Bactrocera carambolae [Diptera: Bactrocera], Nilapavata lugens [Hemiptera: Delphacidae], Sitophilus zeamais [Coleoptera: Curculionidae] dan Plutella xylostella [Lepidoptera: Plutellidae]).…”
Section: Introductionmentioning
confidence: 99%